On the calibration of Bouc-Wen model to describe the viscoelasticity in steady-state rolling tires - Raqueti, Rafael da Silva (2022)
Reducing tire rolling resistance and energy loss is a topic of interest to the tire industry. Understanding and modeling these phenomena are essential to approach this problem and propose robust solutions. This work suggests a model based on the Bouc-Wen model to simulate internal variables from viscoelastic constitutive laws. Furthermore, sensitivity analysis is performed on the Bouc-Wen model parameters to evaluate their influence on the system response and capture the full range of possible values that improve the predictive ability of the suggested model. This task calculates the Sobol’ indices estimated from a Polynomial-Chaos expansion based on the Bouc-Wen parameters. Once the range of feasible model solutions is established, the proposed model is calibrated through Bayesian inference. Finally, the uncertainties are propagated, and the model is validated using data of viscoelastic internal variables from the finite element approximation of a steady-rolling tire provided by Michelin. Satisfactory results are obtained, as the proposed model can simulate viscoelastic internal variables with a reduced computational cost for some branches of interest. Its outputs are in agreement with the finite element approximation data.